Peranan Media Sosial Dalam Partisipasi Politik Mahasiswa Di Era Society 5.0 - Audya Sari, Putri; Saleh, Syarbaini (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
The rapid technological development in the Society 5.0 era has brought about a transformation in digital political participation in Indonesia as well as changes in student political participation patterns. Students, as a young intellectual group, have their own unique ways of using social media for political participation. The purpose of this research is to understand the role of social media in student political participation in the Society 5.0 era. This study employs a qualitative method with a descriptive approach. In the data collection process, this research uses interview and documentation techniques involving 15 students who are engaged in intracampus organizations and students who actively use social media. To test data validity, this study uses a credibility test through source triangulation. The research findings show that Instagram and TikTok social media platforms are widely used for accessing political information. These social media platforms play an important role in shaping students' political awareness. In the Society 5.0 era, forms of student political participation through social media include engagement in online discussions, sharing political posts, and promoting hashtags related to political issues. The challenges of digital political participation include the prevalence of hoax news, buzzers, low literacy levels, and political polarization or conflicting viewpoints that become obstacles in utilizing social media as a space for student political participation.